Combined Stress Conditions in Melon Induce Non-additive Effects in the Core miRNA Regulatory Network - Pascual Villalba-Bermell (Frontiers Media S.A., 2021)
Climate change has been associated with a higher incidence of combined adverse environmental conditions that can promote a significant decrease in crop productivity. However, knowledge on how a combination of stresses might affect plant development is still scarce. MicroRNAs (miRNAs) have been proposed as potential targets for improving crop productivity. Here, we have combined deep-sequencing, computational characterization of responsive miRNAs and validation of their regulatory role in a comprehensive analysis of response of melon to several combinations of four stresses (cold, salinity, short day, and infection with a fungus). Twenty-two miRNA families responding to double and/or triple stresses were identified. The regulatory role of the differentially expressed miRNAs was validated by quantitative measurements of the expression of the corresponding target genes. A high proportion (ca. 60%) of these families (mainly highly conserved miRNAs targeting transcription factors) showed a non-additive response to multiple stresses in comparison with that observed under each one of the stresses individually. Among those miRNAs showing non-additive response to stress combinations, most interactions were negative, suggesting the existence of functional convergence in the miRNA-mediated response to combined stresses. Taken together, our results provide compelling pieces of evidence that the response to combined stresses cannot be easily predicted from the study individual stresses.